2005
DOI: 10.1029/2004jd004649
|View full text |Cite
|
Sign up to set email alerts
|

Time‐ and size‐resolved chemical composition of submicron particles in Pittsburgh: Implications for aerosol sources and processes

Abstract: [1] An Aerodyne aerosol mass spectrometer (AMS) was deployed at the Pittsburgh Environmental Protection Agency Supersite from 7 to 22 September 2002 as part of the Pittsburgh Air Quality Study (PAQS). The main objectives of this deployment were to characterize the concentrations, size distributions, and temporal variations of nonrefractory (NR) chemical species in submicron particles (approximately PM 1 ) and to further develop and evaluate the AMS. Reasonably good agreement was observed on particle concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

80
368
6
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 311 publications
(458 citation statements)
references
References 58 publications
80
368
6
4
Order By: Relevance
“…S3c, the SMPS-measured particle volume correlated strongly with the 17 AMS measured total mass (R 2 = 0.88). The slope from the linear fit of PM1 mass against SMPS 18 volume is 1.24 g/cm 3 , which was lower than the average (± 1) particle density of 1.50 (± 0.08) 19 g/cm 3 estimated using the measured chemical composition in this study (Zhang et al, 2005b) (Fig. 20 S3d).…”
Section: Basic Hr-tof-ams Data Analysis 29contrasting
confidence: 61%
“…S3c, the SMPS-measured particle volume correlated strongly with the 17 AMS measured total mass (R 2 = 0.88). The slope from the linear fit of PM1 mass against SMPS 18 volume is 1.24 g/cm 3 , which was lower than the average (± 1) particle density of 1.50 (± 0.08) 19 g/cm 3 estimated using the measured chemical composition in this study (Zhang et al, 2005b) (Fig. 20 S3d).…”
Section: Basic Hr-tof-ams Data Analysis 29contrasting
confidence: 61%
“…The concentrations of other species are quantified by using ''relative ionization efficiencies'' (RIEs) determined during calibration experiments with those species (Alfarra et al, 2004). Organic species of many different types have very similar RIEs around 1.4 (Takegawa et al, 2005;Zhang et al, 2005). Together with the RIEs and comparing the collected mass spectrum to known fragmentation patterns, the mass from specific species (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…However, when both SO 2 and VOC concentrations were elevated, particle growth exceeded that which could be explained by SO 2 oxidation alone; suggesting the VOCs are incorporated into the aerosols (Brock et al, 2003). However, other field studies have not found a significant difference between the organic mass concentrations between periods when ambient sulfate aerosols were acidic or neutralized (Zhang et al, 2005). Thus, laboratory studies are needed to evaluate the potential importance of this type of reaction in the atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…However, in previous studies using the AMS Drewnick et al, 2004b;Hogrefe et al, 2004;Zhang et al, 2005b) it has been observed that there is a systematic (but highly reproducible) underestimation of the mass concentration of aerosols measured with the AMS when compared to other quantitative aerosol measurements such as the Particle Into Liquid Sampler (PILS) or Scanning Mobility Particle Sizer (SMPS). In these studies, the underestimation in mass concentration observed with the AMS indicates AMS Collection Efficiencies (CE) ranging from 0.43 to 1.…”
Section: Introductionmentioning
confidence: 99%